Alpine community recruitment potential is determined by habitat attributes in the alpine ecosystems of the Himalaya‐Hengduan Mountains, SW China. Issue 23 (18th November 2021) - Chen, Xufang; Qian, Lishen; Zhang, Yazhou; Shi, Honghua; Sun, Hang; Chen, Jianguo
Abstract: The fragility and sensitivity to climate change of alpine ecosystems make it difficult to maintain the stability of their plant communities. Thus, it is important to determine which plant propagules are stored in the soils in order to understand community recruitment potential, especially under different environmental conditions. Based on a soil seed germination and seedling cultivation experiment, we aimed to identify differences in the soil seed attributes between three typical habitat types in the alpine subnival ecosystems of the Himalaya‐Hengduan Mountains and hence to predict the community recruitment potential of each of these different communities. We found that the seed assemblages in the soils differed between habitats. The most abundant taxa were from the genera Saxifraga, Kobresia, Arenaria, Polygonum, Draba, and Viola, while the taxa with lowest abundance were Apiaceae, Campanulaceae, Circaea, Crassulaceae, and Gentiana . Different habitats exhibited variable soil seed richness, diversity, and density. However, the patterns differed between study sites. Specifically, at Baima (BM) and Shika (SK) snow mountains, soil seed richness, diversity, and density were generally highest in grassland, followed by rock bed and bare ground. In contrast, on Jiaozi (JZ) snow mountain, the rock bed supported the highest soil seed richness and density, followed by grassland and bare ground. These results suggest that the attributes of habitats and communities can both affect the accumulation of soil seeds. Bare ground supports the lowest seed diversity and density but also harbors the most empty niches. We, therefore, predict that, once the thermal conditions become suitable as a result of global warming, this habitat has the potential to see greater changes than grassland and rock bed in terms of community recruitment. Abstract : This study identified the differences in the soil seed composition, diversity, and density between three typical habitat types—rock bed, bare ground, and grassland—in the alpine subnival ecosystems on different mountains in the Himalaya‐Hengduan Mountains (HHM). The results not only shed light on the understanding of the current sustainability of alpine communities with different habitat attributes but also contribute a lot to the prediction of potential changes of these communities under future climate warming.